The effectiveness of a new dried human amnion derived membrane in addition to standard care in treating diabetic foot ulcers: A patient and assessor blind, randomised controlled pilot study. Issue 5 (19th February 2021) - Game, Fran; Gray, Katie; Davis, Daniel; Sherman, Rachelle; Chokkalingam, Kamal; Connan, Zak; Fakis, Apostolos; Jones, Michael
Abstract: Recent reviews suggest that amniotic membrane products may accelerate healing of diabetic foot ulcers. A new dried human amniotic membrane (dHAM) has been used for ocular ulcers but not for diabetic foot ulcers. This was a multi‐centre, prospective, patient and observer blind, randomised controlled pilot trial, to investigate whether 2 weekly addition of the dHAM to standard care versus standard care alone increased the proportion of healed participants' index foot ulcers within 12 weeks. Thirty‐one people (mean age 59.8 years, 81% male, 87% type 2 diabetes) were randomised (15 dHAM, 16 usual care). Within 12 weeks, healing occurred in 4 (27%) ulcers in the dHAM group versus 1 (6.3%) usual care group ( P = .1). Percentage wound area reduction was higher in the dHAM versus control group. ( P = .0057). There was no difference in AEs between the two groups. Six participants allocated to dHAM correctly identified their treatment group, although 5 in usual care incorrectly thought they were in the intervention arm. This pilot trial result is encouraging showing that this dHAM preparation is safe and promising treatment. These results will be used to design a statistically powered, definitive double blind randomised controlled trial.